Co-ocupações de bebês e mães para o acompanhamento do desenvolvimento infantil e ocupacional nos primeiros meses de vida: estudo de casos múltiplos por meio de filmagens - Beltrame, Vitória Hoerbe (2022)
Human occupations are the personally significant activities that constitute the subject's daily life, are intentional, and have purposes that influence health and well-being. The child's involvement in occupations in the first months of life depends on another person, usually represented by the mother. The term co-occupation has been used to describe the interactional, joint, and shared exchange between mothers and babies, in occupations such as feeding, bathing, playing, holding, changing clothes, and interactions. Contemporary scholars have problematized the need to produce systematic studies on co-occupations as applied science, defending the existence of three constructs, namely shared physicality, emotionality, and intentionality. Considering the above, the objective of this research was to characterize and describe the co-occupations of feeding, bathing, and playing of babies and mothers in the first months of life, and to identify the implications for the practice of occupational therapists, considering the child and occupational development in early childhood. In order to do so, a multiple case study was analyzed through descriptive and exploratory qualitative research. Data collection was carried out through filming, totaling 17 homemade videos, six of the co-occupation of feeding and bathing and five of the co-occupation of playing, since one of the dyads did not send the footage of the co-occupation of playing. The footage was transcribed and analyzed using the ATLAS ti software, version 9®. In addition, two independent judges analyzed the footage from the perspective of the assessment instrument Indicadores de Referência ao Desenvolvimento Infantil (IRDI) and answered three more questions about the mother and baby interactions. The results indicate that the mother and the baby are mutually engaged in the act of feeding on the part of the mother and being fed on the part of the baby in this co-occupation. In all three studied co-occupations, both engage mutually to interact with regard to the exchange of glances, protoconversations, body contact, and exchanges of smiles. From a sensory and motor perspective, it is pointed out that mutual engagements support the existence of the construct of shared physicality, which also allowed the characterization of the construct of shared emotionality when the co-regulation between the general state of the baby and the mother is perceived in the co-occupations of feeding, bathing, and playing. On the other hand, shared intentionality is affirmed by the baby's active position to interact and react to feelings of hunger, which, when answered by the mother, characterize the construct in all three studied co-occupations. It is also observed, in the co-occupations, the identification of the IRDI indexes, mainly in relation to the co-occupation of playing. It is concluded that co-occupations are important with regard to the stimuli arising from the relationship between the dyads, allowing occupational therapists to carry out readings on mutual engagements and, thus, identify the potential of this relationship to the baby's child and occupational development. It is also worth pointing out that this research was carried out during the COVID-19 pandemic. Hence, it is suggested that field research is carried out with the use of other instruments, such as field diaries and interviews.